2014
DOI: 10.14417/ap.740
|View full text |Cite
|
Sign up to set email alerts
|

Comportamentos extra-diádicos nas relações de namoro: Diferenças de sexo na prevalência e correlatos

Abstract: O presente estudo teve como objetivo avaliar as diferenças de sexo nas taxas de prevalência e nos correlatos dos comportamentos extra-diádicos (CED) offline e online, durante o namoro. A amostra foi constituída por 494 participantes (156 homens e 338 mulheres) com uma idade média de 23.38 anos (DP=3.41). O protocolo de avaliação incluíu os seguintes instrumentos de auto-resposta: Inventário de Comportamentos Extra-Diádicos e Medida Global da Satisfação Relacional e Medida Global da Satisfação Sexual. Cerca de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(73 reference statements)
1
5
0
3
Order By: Relevance
“…In contrast, Liu (2000) reported that such an association only existed for men. Similarly, Martins et al (2014) found that men reporting Catholic religion were more likely to report online EDI. In other studies, religiosity was not related to EDI at all (e.g., Mark et al, 2011;Shaw et al, 2013;Wiederman & Hurd, 1999).…”
Section: Individual Factorsmentioning
confidence: 91%
See 3 more Smart Citations
“…In contrast, Liu (2000) reported that such an association only existed for men. Similarly, Martins et al (2014) found that men reporting Catholic religion were more likely to report online EDI. In other studies, religiosity was not related to EDI at all (e.g., Mark et al, 2011;Shaw et al, 2013;Wiederman & Hurd, 1999).…”
Section: Individual Factorsmentioning
confidence: 91%
“…The association between the level of education and infidelity hasbeenunclear (Allenetal.,2005).Althoughsomestudiesfound an association between higher education and a higher likelihood of infidelity (e.g., Atkins et al, 2001;Traeen & Stigum, 1998;Treas & Giesen, 2000), others reported no significant associations (e.g., Martins et al, 2014;Shaw et al, 2013;Traeen, Holmen, & Stigum, 2007) or opposing findings (e.g., Choi, Catania, & Dolcini, 1994). Another relevant variable is the area of residence.…”
Section: Individual Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2011, this word takes on new proportions when we associate the fact that they are sexually active girls, and that loyalty is reflected in the relationship to avoid STIs, which is a scourge of modern society, namely in Portugal, the second country in Europe with higher values. For these authors, one must also remember that loyalty is a concept that has to be worked with young people and that it starts at home (Martins at al., 2014).…”
Section: Discussionmentioning
confidence: 99%